Heineken N.V. equity research - the Dutch Giant - Godinho, André Filipe Panela (2022)
Heineken is a global company with a very diversified geographic footprint. In the context of an Equity Research Valuation, it’s essential to understand the company and sources its growth. As such this individual report focus on the past performance of the markets, while forecasting its future.